Complications in the decompression of the compressive hemostatic strap: an integrative review (Research, Society and Development, 2023)
Introduction: Cardiac catheterization is an invasive test for diagnosis and/or percutaneous intervention. The use of the radial approach is of great interest as it has numerous advantages and cost-effectiveness. The use of the compressive bracelet as a method of compressive dressing has been increasingly used due to its characteristics that allow better visualization of the puncture site, among others. Objective: To identify evidence in the literature on complications related to the decompression of the compressive hemostatic bracelet by professionals who participate in this specific scenario. Method: This is an integrative review, published in Portuguese, Spanish and English from 2012 to 2022. The search was carried out in the following databases: Latin American and Caribbean Literature in Health Sciences (LILACS), National Library of Medicine USA (MEDLINE) and Scientific Electronic Library On Line (SCIELO) and in the virtual library Banca Virtual de Saúde (BVS) through the Boolean operators AND, NOT and OR. Results: Eleven articles related to the theme were selected and analyzed, 54.54% of the articles showed that the use of the hemostatic bracelet combined with a shorter period of depression is a safe and effective method. Conclusion: The use of the hemostatic bracelet is a safe form of compressive dressing. Such evidence of the method reduces complications related to the access route, such as occlusion of the radial artery, minor bleeding and hematoma.